Pengaruh Rasio Keuangan dan Pertumbuhan Laba terhadap Harga Saham Pada Perusahaan Manufaktur Sub-Sektor Makanan & Minuman tahun 2019 – 2023 yang Terdaftar di Bursa Efek Indonesia (BEI) - Mellinda Agustina; Wawan Andang Saputra (Jurnal Pengabdian Kepada Masyarakat Al-Amin, 2025)
The stock prices of food and beverage companies often draw attention because this sector is considered resilient against economic fluctuations. This study aims to explore the factors that may influence stock price movements by focusing on five main aspects which are profitability, liquidity, solvency, inventory turnover, and earnings growth. The research was conducted on 15 manufacturing companies in the food and beverage sub sector listed on the Indonesia Stock Exchange during the period of 2019 to 2023 with a total of 75 observations. Samples were selected using purposive sampling and the data were processed with SPSS 25 through several stages including descriptive statistics, data quality tests, classical assumption tests, and multiple regression analysis. The findings indicate that profitability and earnings growth have a significant effect on stock prices. In contrast, liquidity, solvency, and inventory turnover do not show a meaningful impact. Nevertheless, when tested simultaneously, all five variables still contribute to stock price movements. This result highlights that external factors beyond the research model may play a more dominant role in shaping the stock performance of food and beverage companies.